2020
DOI: 10.3390/su12187776
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sustainable Marathon Running: The Consumer Socialization Perspective

Abstract: The authors attempt to explain why the generally accepted models built on consumer socialization theory do not sufficiently capture supporting consumer socialization behavior. According to marketing literature, social interaction may influence consumer behavior. The purpose of this study is to understand the behavior of consumers engaged in marathon running. The authors use three types of consumer socialization constructed factors (intergenerational influences, peer influences, and traditional media) and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Unlike Duan et al [18], Hsiao et al [15] considered that social interaction is an important factor that can influence consumer behaviour in marathon events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Duan et al [18], Hsiao et al [15] considered that social interaction is an important factor that can influence consumer behaviour in marathon events.…”
Section: Discussionmentioning
confidence: 99%
“…The same happens to eWOM that will positively affect future intentions [16]. Consumer behaviour is also affected by consumer socialization, notably through intergenerational influence, peer influence, and traditional media [15].…”
Section: Service Quality Of the 2016 Shanghai Internationalmentioning
confidence: 99%
“…Several studies have shown that marathons can lead to deep levels of sports participation and social interaction [ 21 , 22 , 23 ]. Marathons promote social network formation and stimulate sports consumption through social interaction in a way that creates intergenerational influence, peer influence, and media influence [ 24 , 25 ]. During a marathon, runners are able to experience strong emotions and have the opportunity to build social relationships [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The popularity of marathon running has led to an increase in marathon events (Hsiao et al, 2020). The surging enthusiasm for marathon running appears to be due to a number of factors: it has evolved into a physical challenge and an activity that offers recreational and social benefits (Hsiao et al, 2020). It has been established that these events have social and economic benefits and encourage healthy behaviors among people (Alexandris et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After the number of races reached a peak of 666 in 2015, average 12.5 races per week, there has been a slight downward trend in the number of events since then. The possible reasons for this phenomenon could be attributed to high entrance fees, a high number of confusing events (i.e., misgovernment of marathon events), poor quality of events, and people’s attempts to participate in foreign marathon events (Hsiao et al, 2020; Li et al, 2021). Past studies have found that the entrance fee and the quality of events are major concerns for runners (Duan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%